Social Conflict Stemming from Minangkabau Students’ Inadequate Use of Kato Mandaki Communication Ethics and Its Implications for Counseling Services in Society 5.0 - Yusri, Fadhilla; Efrita, Yeni; Suryani, Suryani (KONSELING RELIGI, 2025)
The reduced ability of the younger generation to apply communication ethics contributes to social conflict. This study examines the level of social conflict arising from Minangkabau students’ practice of kato mandaki communication ethics and its implications for counseling services in Society 5.0. Using a descriptive research design with purposive sampling, data were collected from 230 high school students in West Sumatra through a validated social conflict instrument. Data were analyzed using univariate and multivariate techniques via JASP. Results indicate that social conflicts due to improper application of kato mandaki occur at a moderate level, with an average score of 60.63%. Conflicts are more prevalent among students in darek (origin) areas than in rantau (migrant) areas. These findings suggest that integrating local wisdom into school-based counseling services can help mitigate social conflicts and strengthen intergenerational communication. This study provides a foundation for developing culturally responsive counseling programs in the era of Society 5.0.